Through the Magnifying Glass: An Ethnographic Account of the Bilingual Practices of Adolescents in Puerto Rico - MORALES LUGO, KATHERINE RAVENNA (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2019)
This thesis advances research in sociolinguistics by providing an account of the creative bilingual practices found in two high school communities in U.S. territory Puerto Rico. A neo- colonial setting, Puerto Rico offers rich grounds for the analysis of language and identity to take place. This thesis examines English language use under a framework of indexicality known as the ?total linguistic fact? (Silverstein, 1985; 2003): a theory that conceptualizes language as a malleable semiotic tool with the potential of being used towards the construction of social meaning in interaction. This theory simultaneously views language as a flexible tool towards the construction of social identities, or acts of distinction and identification among people. The present study has three interrelated aims. The first is to provide a holistic picture of the distribution of a non-local, prestigious language (English) in a colonialized society. This is done through the incorporation of ethnographic observational methods and extensive fieldwork. The second is to provide a tangible quantitative account of the English linguistic and stylistic practices among Puerto Rican youth. This is done through the incorporation of Muysken?s (2000) typology of bilingual speech which takes into account two overarching manifestations of codemixing: insertion and alternation. Only two of these are identified and discussed in the present corpora, insertion and alternation. These, in turn, are measured against fixed social categories (i.e. class and gender) and locally-constructed, practice-based categories (i.e. peer group affiliation). A more thorough description of specific details of talk is also offered, with some commentary on structural, phonological, and suprasegmental aspects of talk. In this way, the present research also distances itself from other more monolithic and static accounts of bilingualism. The third aim is to provide an identity-based approach to language use through the incorporation of qualitative third-wave methodologies, such as that of conducting micro-analysis of speech through frameworks of style in bilingual practice and theories of indexicality and ideologies of speaking (cf. Silverstein, 2001, 1989; Agha, 2003; Eckert, 2001). In general, results demonstrate that when it comes to the social and symbolic role of English, adopting one method of analysis ? such as observation ? over the other ? such as distribution analysis, offers only partial insight onto the languaging practices that take place in each community. Likewise, discourses of language ideologies, national identities, and cultural alignments provide additional insights so as to understand distribution of language, styles, and users? adoption and/or rejection of English-incorporating practices. Indeed, it was found that particular styles of speaking are laden with ideological undertones to do with assimilation and/or resistance to American culture and notions of Puerto Rican nationalism; simultaneously, discourses demonstrate a gradual shift towards positive orientations of English as ?part of Puerto Rican culture?. Ideologies and languaging styles were also found to vary according to which high school environment they were taking place. Private school settings, in particular, encouraged the idea of English as a desirably quality or language to claim as part of their own, a universal language, and purveyor of greater opportunities. And, indeed, language distribution in private school settings demonstrated a diverse spectrum of bilingual styles: from Spanish dominant, hybrid, to English dominant. Meanwhile, public school settings offered a wider spectrum of language ideologies, yet systematic or hierarchical distributions of language styles. In public school institutions, students who had at some point in their lives received private school education, or belonged to financial stable families were found to engage to a greater extent in bilingual styles and to have a positive disposition to English language, yet their positive disposition to English also co-existed with negative ideologies of the native English speaker or gringo on the island, or the Puerto Rican who tries to ?sound like a gringo?. In this way, the public school setting demonstrated the ideological struggle that is prevalent in much of the literature on the island, and the private school setting follows a more identity-based distribution to different languaging styles, where ?who you are? plays a role in ?what you do? with your language.
APPROVED
Keywords: language and identity; colonialism; bilingualism; indexicality; youth speech; linguistics; late modernity